Analisis Pengelolaan Sarana dan Prasarana Pendidikan Khusus di Dinas Pendidikan Provinsi Sumatera Selatan - Tiara Meftahul Jannah; Sri Rahayu (BINER : Jurnal Ilmu Komputer, Teknik dan Multimedia, 2025)
Management of facilities and infrastructure is an essential factor in supporting the success of educational services for students with special needs. This study was conducted at the Facilities and Infrastructure Division of the Special Education and Special Services (PKLK) Department of the South Sumatera Provincial Education Office to identify the current management practices, examine existing challenges, and formulate solutions for improving effectiveness and accuracy in implementation. The research employed a descriptive qualitative method through observations, interviews, and document analysis. The findings indicate that although the management workflow already follows established procedures, several obstacles persist. The most significant issues include manual data collection, uneven distribution of resources, and limited monitoring and evaluation due to insufficient human resources and the absence of an integrated information system. Furthermore, procurement delays have contributed to slow fulfillment of educational support tools for special schools. Based on the results, this study recommends developing a digital-based data management system, simplifying approval procedures, and improving coordination and training for personnel to enhance efficiency, accountability, and sustainability in facility management. The results are expected to serve as a reference and evaluation material for improving special education service strategies in South Sumatera.